Pengaruh Penerapan Sistem E-Filling, Pengetahuan, Sosialisasi, Kesadaran, Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Pekerja Bebas - Muhamad Mahfud; Khoirina Farina (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Tax Compliance is a submissive or obedience attitude where the taxplayer has to fulfill all the tax right and obligations. The purpose of this research is to verify the factor that affect taxplayer compliance using the e-filing system, knowledge, socialization, awareness and tax sanctions on the compliance of freelance taxpayers. Data collection method in this research is by using a questionnaire. The population in this research is freelance taxpayers. The sampling method in this study used convience sampling and obtained as many as 71 respondents that fit the criteria. This study uses PLS SEM with the SmartPLS version 4.0 application for data analysis. The results of this research show that the implementation of the e-filing system, knowledge, socialization, awareness and tax sanctions have a positive and significant effect on taxpayer compliance as freelancers.